Workshop Teknik Penulisan Soal Di SD 66 Mambo - Anidi Anidi; Fernandes Arung (Prodi PGSD Unsultra, 2025)
Good quality questions greatly affect the effectiveness of assessment in learning. However, many teachers still face obstacles in compiling questions that are in accordance with the correct writing rules. This community service activity aims to improve teacher competence in writing quality questions through a workshop at SD 66 Mambo. The method used is direct training and mentoring with theoretical and practical approaches. The results of the activity showed that the participants experienced an increase in understanding in compiling questions according to the principles of validity, reliability, distinguishing power, and level of difficulty. This workshop provides significant benefits for teachers in compiling more effective assessment instruments to improve the quality of learning in schools.